Ocrelizumab Extended Interval Dosing in Multiple Sclerosis in Times of COVID-19. Issue 5 (September 2021) - Rolfes, Leoni; Pawlitzki, Marc; Pfeuffer, Steffen; Nelke, Christopher; Lux, Anke; Pul, Refik; Kleinschnitz, Christoph; Kleinschnitz, Konstanze; Rogall, Rebeca; Pape, Katrin; Bittner, Stefan; Zipp, Frauke; et al.
Abstract : Objective: To evaluate the clinical consequences of extended interval dosing (EID) of ocrelizumab in relapsing-remitting multiple sclerosis (RRMS) during the coronavirus disease 2019 (COVID-19) pandemic. Methods: In our retrospective, multicenter cohort study, we compared patients with RRMS on EID (defined as ≥4-week delay of dose interval) with a control group on standard interval dosing (SID) at the same period (January to December 2020). Results: Three hundred eighteen patients with RRMS were longitudinally evaluated in 5 German centers. One hundred sixteen patients received ocrelizumab on EID (median delay [interquartile range 8.68 [5.09–13.07] weeks). Three months after the last ocrelizumab infusion, 182 (90.1%) patients following SID and 105 (90.5%) EID patients remained relapse free ( p = 0.903). Three-month confirmed progression of disability was observed in 18 SID patients (8.9%) and 11 EID patients (9.5%, p = 0.433). MRI progression was documented in 9 SID patients (4.5%) and 8 EID patients (6.9%) at 3-month follow-up ( p = 0.232). Multivariate logistic regression showed no association between treatment regimen and no evidence of disease activity status at follow-up (OR: 1.266 [95% CI: 0.695–2.305]; p = 0.441). Clinical stability was accompanied by persistent peripheral CD19 + B-cell depletion in both groups (SID vs EID: 82.6% vs 83.3%, p = 0.463). Disease activity in our cohort was not associated with CD19 + B-cell repopulation. Conclusion: Our data support EID of ocrelizumab as potential risk mitigation strategy in times of the COVID-19 pandemic. Classification of Evidence: This study provides Class IV evidence that for patients with RRMS, an EID of at least 4 weeks does not diminish effectiveness of ocrelizumab.